2012
DOI: 10.1172/jci57313
|View full text |Cite
|
Sign up to set email alerts
|

The CXCR4/CXCR7/SDF-1 pathway contributes to the pathogenesis of Shiga toxin–associated hemolytic uremic syndrome in humans and mice

Abstract: Hemolytic uremic syndrome (HUS) is a potentially life-threatening condition. It often occurs after gastro-intestinal infection with E. coli O157:H7, which produces Shiga toxins (Stx) that cause hemolytic anemia, thrombocytopenia, and renal injury. Stx-mediated changes in endothelial phenotype have been linked to the pathogenesis of HUS. Here we report our studies investigating Stx-induced changes in gene expression and their contribution to the pathogenesis of HUS. Stx function by inactivating host ribosomes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 80 publications
(107 reference statements)
2
66
1
Order By: Relevance
“…We also found no hematological evidence of thrombotic disease, such as prolonged clotting time or fibrin D-dimer formation. Following systemic administration of Stx, mice that are deficient in ADAMTS13, a protease that cleaves the hemostatic von Willebrand factor, demonstrate wide strain-specific variation in the degree of microvascular thrombosis, thrombocytopenia, and hemolytic anemia (88,101). It is possible that infection by C. rodentium (λstx 2dact ) might trigger more overt microangiopathy and thus more closely resemble human HUS, in murine strains different from the C57BL/6 strain utilized here.…”
Section: Figurementioning
confidence: 92%
“…We also found no hematological evidence of thrombotic disease, such as prolonged clotting time or fibrin D-dimer formation. Following systemic administration of Stx, mice that are deficient in ADAMTS13, a protease that cleaves the hemostatic von Willebrand factor, demonstrate wide strain-specific variation in the degree of microvascular thrombosis, thrombocytopenia, and hemolytic anemia (88,101). It is possible that infection by C. rodentium (λstx 2dact ) might trigger more overt microangiopathy and thus more closely resemble human HUS, in murine strains different from the C57BL/6 strain utilized here.…”
Section: Figurementioning
confidence: 92%
“…In a murine model of shiga-toxin exposure, the CXCL12/CXCR4 interaction appeared to increase endothelial permeability (11), whereas this same interaction has also been shown to attenuate thrombin-induced endothelial permeability through phosphoinositide 3-kinase (PI3K) and Rac1 activation (10). Our previous studies have demonstrated that the analogue SDF-1α cyclic peptide known as CTCE 0214 (CTCE) improved endothelial barrier integrity in the cecal ligation and puncture (CLP) model of murine sepsis (12,13).…”
Section: Transfection Of Hmvecmentioning
confidence: 99%
“…The renal lesion in HUS patients consists of thrombi in glomerular capillaries, swelling and detachment of endothelial cells from the basement membrane (14), and extensive tubular injury (4,12). Mouse models of EHEC infection or Stx injection reproduce certain aspects of this lesion with platelet deposition in glomeruli (15,16), damaged glomerular capillaries (17), and pronounced tubular damage (7,18). In addition to severe renal damage, 20-50% of patients with HUS develop neurologic manifestations ranging from mild symptoms to coma and stroke and affecting various regions of the brain (19,20).…”
mentioning
confidence: 99%